## moli1993 one year ago simplify the following using Boolean algebra. (xy)'+xz'+yz a)y+z' b)x+y c)X'+y d)xz'

1. moli1993

c) x'+y

2. ybarrap

\$\$ \Large{ (xy)'+xz'+yz\\ =[(xy)(xz')'(yz)']'\\ =[(xy)(x'+z)(y'+z')]'\\ =[((xyx')+(xyz))(y'+z')]'\\ =[0+xyzy'+xyzz']'\\ =[0+0+0]'\\ =[0]'\\ =1 } \$\$ This is a tautology, because it is always true. Here is another method using a Truth Table |dw:1395590669537:dw| This also shows a tautology

3. ybarrap

Does this make sense?

4. AkashdeepDeb

(xy)' + xz' + yz We know that (xy)' = x' + y' [De morgan's laws] x' + y' + xz' + yz x' + z' + y' + z x' + y' + 1 = 1 None of the options are as 1 @ybarrap Is truth table the only method to find that out?

5. AkashdeepDeb

@moli1993 I guess you have to see which of the options also show Tautology [Always true].

6. ybarrap

The truth table is authoritative. This is a tautology. None of the options are a tautology so they are all incorrect.

7. moli1993

I am so sorry , wrote the wrong question here :- it is (xz)'+xz'+yz and the options are same as given earlier !

8. ybarrap

It's the same process

9. moli1993

process is same but it's not a tautology i suppose !

10. dumbcow

(xz)' = x' + z' z' +xz' = z'(1+x) = z' --> x' + z' + yz = x' +z' +z = x' + 1 = 1

11. moli1993

how x' + z' + yz = x' +z' +z

12. AkashdeepDeb

(xz)'+xz'+yz We know that (xz)' = x' + z' [De morgan's laws] x' + z' + xz' + yz x' + (z' + xz') + yz [ In z' + xz' take z' common, z'(1+x) = z'(1) = z' ] x' + z' + yz [yz = zy] z' + zy + x' Using simplification law [A + A'B = A+B] we get, z' + y + x' Final answer should be x' + y + z'

13. moli1993

but it doesnt matches any of the options given above

14. AkashdeepDeb

(xz)' + y I am pretty sure, this is the final answer. :/ @ybarrap @dumbcow ?

15. moli1993

me too I think u r correct !

16. dumbcow
17. ybarrap

yes it is

18. moli1993

Thank you all for helping me !

19. AkashdeepDeb

:)

Find more explanations on OpenStudy